Anti-Inflammatory Activity of the Marine Cyanobacterium against Carrageenan-Induced Paw Oedema in Wistar Albino Rats - G. Silambarasan; T. Ramanathan; M.A. Nabeel; V.K. Kalaichelvan; K. Kathiresan; T. Balasubramanian (European Journal of Inflammation, 2011)
Inflammatory diseases, including rheumatic, diseases are a major cause of morbidity of the working force throughout the world. Inflammation is a tissue reaction to infection. The effects are redness (erythema), swelling (oedema) and pain, to the area that can result in loss of function. Cyanobacteria are photosynthetic prokaryotic organisms which are potentially useful in pharmaceuticals, industrial chemicals, and restriction enzymes. Trichodesmium species are non-heterocystous cyanobacteria, commonly found in tropical and subtropical oligotrophic oceans. They occur in filaments of 20–200 cells which often congregate to form larger colonies called blooms that can be seen and often form dense blooms covering vast areas in sub-tropical regions. The present study tested the anti-inflammatory effect of the marine cyanobacterium, Trichodesmium erythraeum in carrageenan-induced inflammation in rats. The aqueous extract showed anti-inflammatory activity at a high dosage (500 mg/kg) and this effect was on par with the commercial drug, indomethacin. The inhibition of inflammation volume was 57.5±5.5 % and 47.5±4.7% respectively, at higher and lower dosages, in 30 minutes of treatment. The control group without any treatment exhibited an increase in the paw volume. This is the first report on the anti-inflammatory effect of marine-derived Trichodesmium erythraeum .